Blade bound : a Chicagoland vampires novel - Neill, Chloe (Neill, Chloe. Chicagoland vampires novel., 2017)
"The thrilling final installment of Chloe Neill's New York Times bestselling urban fantasy series sees sinister sorcery advancing across Chicago, and it might usher in the fall of Cadogan House.... Since the night of her brutal attack and unwilling transformation into a vampire, Merit has stood as Sentinel and protector of Chicago's Cadogan House. She's saved the Windy City from the forces of darkness time and again with her liege and lover, Ethan Sullivan, by her side. When the House is infiltrated andMerit is attacked by a vampire who seems to be under the sway of dark magic, Merit and Ethan realize the danger is closer than they could have imagined. As malign sorcery spreads throughout the city, Merit must go to war against supernatural powers beyond her comprehension. It is her last chance to save everything--and everyone--she loves"--